Relative satisfaction index on students’ satisfaction towards hostel facilities - Mansor, Rosnalini; Zaini, Bahtiar Jamili; Sarkawi, Mohammad Nizam; Lee, Ee Phay (The Mattingley Publishing Co., Inc., 2020)
This study aims to determine the level of satisfaction among undergraduate students based on Relative Satisfaction Index (RSI) on hostel facilities. The RSI on its facilities will be compared between students who stay outside the campus and students who stay inside the campus, and also among the 2genders. The study uses a survey based on the questionnaire administered to280 respondents (undergraduate students) who stayed at a hostel provided by a university in Malaysia. By using descriptive analysis, the levels of satisfaction among the respondents (undergraduate students) on the hostel facilities are identified and examined. The data analysis indicates that the levels of satisfaction between undergraduate students are mixed. Nevertheless, on average the students’ satisfaction levels are considered fair towards the facilities provided by the university based on the values of RSI (0.51 and 0.79). The data analysis and research results will assist the university to enhance its facilities to improve the students’ satisfaction.